Double-sided adhesive tape
By using polymers containing polar functional groups and specific adhesive layers in the double-sided adhesive tape, the problem of degradation of impact absorption performance of the adhesive tape in the low temperature region in the prior art is solved, and the entire temperature range is achieved. High-efficiency impact absorption effect, suitable for use in monitors and other applications.
Patent Information
- Application Number
- CN202180030239.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-14
- Filing Date
- 2021-04-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-04-16
AI Technical Summary
The impact absorption performance of existing impact absorbing adhesive tapes in low temperature regions is degraded, making it difficult to maintain high efficiency over the entire wide temperature range.
The design of a double-sided adhesive tape is adopted, in which the substrate layer and the adhesive layer have excellent energy storage modulus in the range of -25°C to 120°C, and includes a polymer containing polar functional groups and a specific adhesive layer. Ensure high impact absorption performance under low temperature conditions.
It achieves excellent impact absorption performance over the entire wide temperature range, especially in low temperature regions, and is suitable for applications such as displays.
Smart Images

Figure CN115427524B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a double-sided adhesive tape. Background Art
[0002] If a device with a display is subjected to an impact such as being dropped, there is a problem that the display screen may be cracked.
[0003] Therefore, for the purpose of absorbing such impact, it has been proposed to use a double-sided pressure-sensitive adhesive tape having excellent impact absorption properties (for example, Patent Document 1).
[0004] However, conventional impact-absorbing pressure-sensitive adhesive tapes have a problem of reduced impact absorption over a wide temperature range, particularly in a low-temperature region.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-94575 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] An object of the present invention is to provide a double-sided pressure-sensitive adhesive tape having excellent impact absorption properties over a wide temperature range, particularly in a low temperature region.
[0010] Solutions for solving problems
[0011] The double-sided adhesive tape of the present invention is a double-sided adhesive tape having adhesive layers on both sides of a substrate layer.
[0012] The storage modulus E' of the double-sided adhesive tape as a whole, measured at -25°C to 120°C at a frequency of 1 Hz, is 1.0×10 5 Pa~1.0×10 8 Within the range of Pa.
[0013] In one embodiment, the storage modulus E' of the substrate layer measured at -25°C to 120°C and at a frequency of 1 Hz is 1.0×10 5 Pa~1.0×10 8 Within the range of Pa.
[0014] In one embodiment, the maximum value of the storage modulus G' of the adhesive layer measured at -25°C to 120°C and at a frequency of 1 Hz is 1.0×10 10 Below Pa.
[0015] In one embodiment, the adhesive force of the adhesive layer to a SUS plate when subjected to 180-degree peeling at a tensile speed of 300 mm / min at 23° C. and 50% RH is 5 N / 20 mm or more.
[0016] In one embodiment, the base layer includes at least one polar functional group-containing polymer selected from the group consisting of condensation polymers and addition polymers.
[0017] In one embodiment, the polar functional group-containing polymer is at least one selected from the group consisting of polyamide, polyurethane, and polyurea.
[0018] In one embodiment, the polar functional group-containing polymer has at least one selected from the group consisting of an ether bond and an ester bond.
[0019] In one embodiment, the pressure-sensitive adhesive layer includes at least one selected from the group consisting of acrylic pressure-sensitive adhesives, rubber pressure-sensitive adhesives, silicone pressure-sensitive adhesives, and urethane pressure-sensitive adhesives.
[0020] In one embodiment, the pressure-sensitive adhesive tape of the present invention is an impact-absorbing tape for displays.
[0021] Effects of the Invention
[0022] According to the present invention, it is possible to provide a double-sided pressure-sensitive adhesive tape having excellent impact absorption properties over a wide temperature range, particularly in a low temperature region. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic cross-sectional view showing one embodiment of the double-sided adhesive tape of the present invention. DETAILED DESCRIPTION
[0024] 《《Double-Sided Adhesive Tape》》
[0025] The double-sided adhesive tape according to the embodiment of the present invention is an adhesive tape having adhesive layers on both sides of the substrate layer. Figure 1 1 , a double-sided adhesive tape is shown having adhesive layers 200 a and 200 b on both sides of a base layer 100 .
[0026] The adhesive layer 200 a and the adhesive layer 200 b may have the same composition as each other or may have different compositions.
[0027] The adhesive layer 200 a and the adhesive layer 200 b may have the same thickness or different thicknesses.
[0028] The substrate layer may be a single layer or may be two or more layers. From the viewpoint of further expressing the effects of the present invention, the substrate layer is preferably a single layer.
[0029] The adhesive layer may be a single layer or may be two or more layers. From the viewpoint of further expressing the effects of the present invention, the adhesive layer is preferably a single layer.
[0030] The double-sided pressure-sensitive adhesive tape according to the embodiment of the present invention may have any appropriate other layer in addition to the base material layer and the pressure-sensitive adhesive layer, within a range not impairing the effects of the present invention.
[0031] The double-sided pressure-sensitive adhesive tape according to the embodiment of the present invention may include any appropriate release liner on the surface of the pressure-sensitive adhesive layer opposite to the substrate layer for the purpose of protecting the pressure-sensitive adhesive until use.
[0032] Examples of the release liner include release liners obtained by subjecting the surface of a substrate (liner substrate) such as paper or plastic film to a silicone treatment, and release liners obtained by laminating the surface of a substrate (liner substrate) such as paper or plastic film with a polyolefin resin. Examples of the plastic film used as the liner substrate include polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, and ethylene-vinyl acetate copolymer film.
[0033] The thickness of the release liner is preferably 1 μm to 500 μm, more preferably 3 μm to 450 μm, further preferably 5 μm to 400 μm, and particularly preferably 10 μm to 300 μm.
[0034] The release liner is preferably subjected to a release treatment on at least one surface. Any appropriate release treatment may be adopted as the release treatment within a range not impairing the effects of the present invention.
[0035] The total thickness d of the double-sided adhesive tape of the embodiment of the present invention is preferably 1 μm to 500 μm, more preferably 5 μm to 450 μm, further preferably 10 μm to 400 μm, particularly preferably 15 μm to 350 μm, and most preferably 30 μm to 300 μm. When the total thickness d of the double-sided adhesive tape of the embodiment of the present invention is within the above range, the effect of the present invention can be further manifested.
[0036] The double-sided adhesive tape according to the embodiment of the present invention has a storage modulus E' of 1.0×10 5 Pa~1.0×10 8 The storage modulus E' is preferably 3.0×10 5 Pa~1.0×10 8 Pa, more preferably 5×10 5Pa~1.0×10 8 Pa, more preferably 8.0×10 5 Pa~9.9×10 7 Pa, particularly preferably 1.0×10 6 Pa~9.85×10 7 When the storage elastic modulus E' of the entire double-sided adhesive tape is within the above range, a double-sided adhesive tape having excellent impact absorption properties over a wide temperature range, particularly in a low temperature region, can be provided.
[0037] The double-sided adhesive tape of the embodiment of the present invention preferably has a storage modulus E' of 1.0×10 8 Pa or less, more preferably 9.9×10 7 Pa or less, more preferably 9.75×10 7 Pa or less, particularly preferably 9.6×10 7 The lower limit of the storage modulus E' measured at -25°C and a frequency of 1 Hz is preferably 5.0×10 6 When the storage elastic modulus E' of the entire double-sided adhesive tape measured at -25°C and a frequency of 1 Hz is within the above range, a double-sided adhesive tape having excellent impact absorption properties over a wide temperature range, particularly in a low temperature region, can be provided.
[0038] The double-sided adhesive tape according to the embodiment of the present invention preferably has a storage modulus E' of 1.0×10 8 Pa or less, more preferably 3.0×10 6 Pa or less, more preferably 2.5×10 6 Pa or less, particularly preferably 2.3×10 6 The lower limit of the storage modulus E' measured at 23°C and a frequency of 1 Hz is preferably 5.0×10 5 When the storage elastic modulus E' of the entire double-sided adhesive tape measured at 23°C and a frequency of 1 Hz is within the above range, a double-sided adhesive tape having excellent impact absorption properties over a wide temperature range, particularly in a low temperature region, can be provided.
[0039] The double-sided adhesive tape according to the embodiment of the present invention preferably has a storage modulus E' of 1.0×10 8 Pa or less, more preferably 3.0×10 6 Pa or less, more preferably 2.9×10 6The lower limit of the storage modulus E' measured at 80°C and a frequency of 1 Hz is preferably 5.0×10 5 When the storage elastic modulus E' of the entire double-sided adhesive tape measured at 80°C and a frequency of 1 Hz is within the above range, a double-sided adhesive tape having excellent impact absorption properties over a wide temperature range, particularly in a low temperature region, can be provided.
[0040] For the double-sided adhesive tape of the embodiment of the present invention, the ratio of the storage modulus E' measured at -25°C with a frequency of 1 Hz to the storage modulus E' measured at 0°C with a frequency of 1 Hz (storage modulus E'(-25°C) / storage modulus E'(80°C)) of the double-sided adhesive tape as a whole is preferably 40.0 or less, more preferably 35.0 or less, further preferably 30.0 or less, and particularly preferably 18.0 or less. The lower limit of the above ratio (storage modulus E'(-25°C) / storage modulus E'(80°C)) is preferably 1.0 or more. When the ratio of the storage modulus E' measured at a frequency of 1 Hz at -25°C to the storage modulus E' measured at a frequency of 1 Hz at 0°C (storage modulus E'(-25°C) / storage modulus E'(80°C)) of the double-sided adhesive tape as a whole is within the above range, it is possible to provide a double-sided adhesive tape having better impact absorption properties over a wide temperature range, particularly in a low temperature region.
[0041] The storage modulus E' of the substrate layer of the double-sided adhesive tape according to the embodiment of the present invention measured at a frequency of 1 Hz at -25°C to 120°C is preferably 1.0×10 5 Pa~1.0×10 8 Pa, more preferably 3.0×10 5 Pa~8.0×10 7 Pa, more preferably 5.0×10 5 Pa~5.0×10 7 Pa, particularly preferably 1.0×10 6 Pa~2.0×10 7 When the storage elastic modulus E' of the substrate layer is within the above range, a double-sided adhesive tape having excellent impact absorption properties over a wide temperature range, particularly in a low temperature region, can be provided.
[0042] The maximum value of the storage modulus G' of the pressure-sensitive adhesive layer of the double-sided pressure-sensitive adhesive tape according to the embodiment of the present invention measured at a frequency of 1 Hz at -25°C to 120°C is preferably 1.0×10 10 Pa or less, more preferably 1.0×10 2 Pa~5.0×10 9 Pa, more preferably 5.0×10 2Pa~1.0×10 9 Pa, particularly preferably 1.0×10 3 Pa~7.0×10 8 When the maximum value of the storage elastic modulus G' of the adhesive layer is within the above range, a double-sided adhesive tape having excellent impact absorption properties over a wide temperature range, particularly in a low temperature region, can be provided.
[0043] The adhesive force of the adhesive layer of the double-sided adhesive tape of the embodiment of the present invention to the SUS plate when peeled at 180 degrees at 23°C and 50%RH at a tensile speed of 300mm / min is preferably 5N / 20mm or more, more preferably 5N / 20mm to 100N / 20mm, further preferably 5N / 20mm to 50N / 20mm, particularly preferably 5N / 20mm to 30N / 20mm, and most preferably 5N / 20mm to 20N / 20mm. When the adhesive force of the adhesive layer to the SUS plate when peeled at 180 degrees at 23°C and 50%RH at a tensile speed of 300mm / min is within the above range, a double-sided adhesive tape with better impact absorption in a wide temperature range, especially in a low temperature region, can be provided.
[0044] 《Base material layer》
[0045] The thickness of the substrate layer is preferably 1 μm to 500 μm, more preferably 2 μm to 400 μm, further preferably 3 μm to 300 μm, and particularly preferably 5 μm to 200 μm. When the thickness of the substrate layer is within the above range, a double-sided adhesive tape having better impact absorption properties can be provided over a wide temperature range, particularly in a low temperature region.
[0046] As the material of the substrate layer, any appropriate material can be adopted within the scope of not impairing the effect of the present invention. As such a material, it is preferred to include at least one polymer containing a polar functional group selected from condensation polymers and addition polymers. That is, the substrate layer preferably includes at least one polymer containing a polar functional group selected from condensation polymers and addition polymers.
[0047] From the perspective of further demonstrating the effects of the present invention, the content ratio of at least one polar functional group-containing polymer selected from condensation polymers and addition polymers in the substrate layer is preferably 50% to 100% by weight, more preferably 70% to 100% by weight, further preferably 90% to 100% by weight, particularly preferably 95% to 100% by weight, and most preferably 98% to 100% by weight.
[0048] At least one polymer containing polar functional groups selected from condensation polymers and addition polymers has polar functional groups such as carbonyl in the main chain of the polymer, and a stronger intermolecular force than that of free radical polymerization polymers works, and can have a network structure that does not rely on covalent bonds. The elasticity of a large number of polymers with a network structure that relies on covalent bonds will become too high, and the concave-convex tracking property may be reduced. For condensation polymers and addition polymers with a network structure that does not rely on covalent bonds, the intermolecular force based on the polar functional group is weak compared to the intermolecular force generated by covalent bonds, and even a smaller energy (energy such as work done by stress, etc.) is easy to relax stress through deformation, etc. After relaxation, the intermolecular force works again between the polar functional groups (for example, the combination of polar functional groups that generate intermolecular forces changes), and a double-sided adhesive tape with better impact absorption can be provided over a wide temperature range, especially in a low temperature region.
[0049] The polymer containing polar functional groups is preferably at least one selected from polyamide, polyurethane, and polyurea. The intermolecular force of the polymer containing hydrogen-bonding polar functional groups (more correctly, hydrogen-bonding polar functional groups with hydrogen-donating property) such as polyamide, polyurethane, and polyurea can be cut off by about 1 / 10 of the energy of the covalent bond (the combination of hydrogen-bonding functional groups that generate intermolecular force changes), and the energy generated by the work done by the heat energy provided at room temperature, the stress generated by bending, etc., can effectively cause the cutting of the intermolecular force. Therefore, it is possible to provide a double-sided adhesive tape with better impact absorption in a wide temperature range, especially in a low temperature region.
[0050] The substrate layer more preferably contains a polar functional group-containing polymer which is an addition polymer. In addition polymers, monomers having various functional groups can be used, and the operation of converting monomers into polymers is easy. Utilizing these features, various properties can be imparted to addition polymers.
[0051] The polar functional group-containing polymer as the addition polymer may have at least one selected from an ether bond and an ester bond. The ether bond may be introduced by using a monomer having an ether bond when obtaining the addition polymer. The ester bond may be introduced by using a monomer having an ester bond when obtaining the addition polymer. For example, when polyurethane is used as the polar functional group-containing polymer, examples of the polyurethane having an ether bond include ether polyurethane. Examples of the polyurethane having an ester bond include ester polyurethane.
[0052] As ether polyurethane, for example, urethane acrylate resin can be cited. Urethane acrylate resin can be obtained, for example, as follows: a precursor containing a polyether segment, a (meth) acrylic segment and a urethane segment is polymerized under a condition that the molecular weight can be controlled to obtain an oligomer, then various additives are added thereto to prepare a coating composition for forming a resin film, which is applied to a supporting substrate and cross-linked, thereby obtaining a urethane acrylate resin film on the supporting substrate. More specifically, it can be obtained as follows: a polyether polyol, a compound containing an isocyanate group and a (meth) acrylic acid hydroxyalkyl ester are polymerized in advance, or an acrylic modified polyether polyol and a compound containing an isocyanate group are pre-polymerized to prepare a urethane acrylate oligomer, and an additive is appropriately added thereto to prepare a coating composition for forming a resin film, which is applied to a supporting substrate and cross-linked, thereby obtaining a urethane acrylate resin film on the supporting substrate.
[0053] Examples of the polyether polyol include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol, and various derivatives thereof.
[0054] As a hydroxyalkyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, etc. are mentioned, for example.
[0055] As the compound containing an isocyanate group, for example, a resin containing an isocyanate group, an oligomer containing an isocyanate group, and a monomer containing an isocyanate group can be cited. As the compound containing an isocyanate group, for example, (poly)isocyanates such as methylenebis-4-cyclohexyl isocyanate, trimethylolpropane adducts of toluene diisocyanate, trimethylolpropane adducts of hexamethylene diisocyanate, trimethylolpropane adducts of isophorone diisocyanate, isocyanurate bodies of toluene diisocyanate, isocyanurate bodies of hexamethylene diisocyanate, and biuret bodies of hexamethylene isocyanate, and blocked products of these isocyanates can be cited.
[0056] Examples of the ester polyurethane include adipate-based (ester-based) polyurethane and polycaprolactone-based (ester-based) polyurethane.
[0057] When a monomer having an ether bond is used to obtain an addition polymer, the elasticity of the addition polymer can be weakened and the molecule can be given flexibility. When a monomer having an ester bond is used to obtain an addition polymer, rigidity can be given to the addition polymer. Therefore, for example, by appropriately combining or using a monomer having an ether bond and a monomer having an ester bond to obtain an addition polymer, the elasticity and rigidity of the addition polymer can be adjusted, and a double-sided adhesive tape with better impact absorption properties over a wide temperature range, particularly in a low temperature range, can be obtained.
[0058] When polyurethane (preferably ether polyurethane or ester polyurethane) is used as the polymer containing polar functional groups, a hydroxyl-containing monomer can be used when obtaining the polyurethane. If a hydroxyl-containing monomer is used when obtaining the polyurethane, the isocyanate monomer used in the addition polymerization reaction when obtaining the polyurethane will react with the hydroxyl-containing monomer, thereby introducing a covalent bond network structure. In addition, the hydroxyl-containing monomer can be added as a raw material of the polyurethane at one time, which can simplify the work of adding after preparing the raw materials of the polyurethane.
[0059] As the polymer containing a polar functional group, polyurethane (preferably ether polyurethane and ester polyurethane) is preferred from the viewpoint of being able to further demonstrate the effect of the present invention. Polyurethane is a polymer compound synthesized by subjecting a polyol (e.g., diol) and a polyisocyanate (e.g., diisocyanate) to a polyaddition reaction at a predetermined ratio.
[0060] As polyurethane (preferably ether polyurethane and ester polyurethane), thermoplastic polyurethane (TPU) and thermosetting polyurethane can be listed. Thermosetting polyurethane is preferred from the perspective of being able to provide a double-sided adhesive tape with better impact absorption in a wide temperature range, especially in a low temperature region. From the perspective of being able to further demonstrate the effect of the present invention, the thermosetting polyurethane is preferably at least one selected from the group consisting of thermosetting ether polyurethane and thermosetting ester polyurethane, and more preferably at least one selected from thermosetting urethane acrylate resin and thermosetting polycaprolactone (ester) polyurethane resin.
[0061] Examples of polyols that can be used for the synthesis of polyurethane include: glycols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,8-octanediol, polyoxytetramethylene glycol, diethylene glycol, polyethylene glycol, and polypropylene glycol; polyester polyols that are polycondensates of the above glycols and dicarboxylic acids (e.g., adipic acid, azelaic acid, and sebacic acid); carbonate glycols such as polyalkylene carbonate diols; etc. These may be either one or two or more.
[0062] Examples of the polyisocyanate that can be used for the synthesis of polyurethane include aromatic, aliphatic, and alicyclic diisocyanates, and polymers (for example, dimers and trimers) of these diisocyanates. Examples of the diisocyanate include tolylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, butane-1,4-diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, dicyclohexylmethane-4,4-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, methylcyclohexane diisocyanate, and m-tetramethylxylylene diisocyanate. These may be either one or two or more.
[0063] In addition to polyols and polyisocyanates, other copolymer components can also be introduced into the polyurethane. As other copolymer components, monocarboxylic acids, dicarboxylic acids, trifunctional or higher polycarboxylic acids, hydroxycarboxylic acids, alkoxycarboxylic acids, and their derivatives can be listed. Other copolymer components can be only one or more. The content ratio of other copolymer components in the polyurethane is preferably less than 30% by weight, more preferably less than 10% by weight, and further preferably less than 5% by weight.
[0064] Adhesive layer
[0065] The thickness of the adhesive layer is preferably 1 μm to 500 μm, more preferably 3 μm to 300 μm, further preferably 5 μm to 200 μm, and particularly preferably 10 μm to 120 μm. When the thickness of the adhesive layer is within the above range, a double-sided adhesive tape having better impact absorption properties can be provided over a wide temperature range, particularly in a low temperature region.
[0066] The adhesive layer includes a base polymer. The base polymer may be only one or more than two. From the perspective of further demonstrating the effect of the present invention, the content ratio of the base polymer in the adhesive layer is preferably 30% to 95% by weight, more preferably 40% to 90% by weight, and further preferably 50% to 80% by weight.
[0067] From the perspective of being able to further demonstrate the effects of the present invention, as the base polymer, preferably at least one selected from acrylic polymers, rubber polymers, silicone polymers, and urethane polymers can be cited. That is, the adhesive layer preferably contains at least one selected from acrylic adhesives containing acrylic polymers, rubber adhesives containing rubber polymers, silicone adhesives containing silicone polymers, and urethane adhesives containing urethane polymers. Hereinafter, as a representative example, the acrylic adhesive is described in detail.
[0068] <Acrylic Adhesive>
[0069] The acrylic adhesive contains an acrylic polymer as a base polymer. The acrylic adhesive may contain a tackifying resin. The acrylic adhesive may also contain a crosslinking agent.
[0070] When the acrylic adhesive contains an acrylic polymer, a tackifier resin and a cross-linking agent, from the perspective of further manifesting the effects of the present invention, the content ratio of the total amount of the acrylic polymer, the tackifier resin and the cross-linking agent relative to the total amount of the acrylic adhesive is preferably 95% by weight or more, more preferably 97% by weight or more, and even more preferably 99% by weight or more.
[0071] (Acrylic polymer)
[0072] The acrylic polymer is preferably a polymer containing an alkyl (meth)acrylate as a main monomer and a monomer component that may further contain a secondary monomer copolymerizable with the main monomer. Here, the main monomer refers to a component that occupies more than 50% by weight of the entire monomer component.
[0073] As the (meth)acrylic acid alkyl ester, for example, a compound represented by the following formula (1) can be preferably used.
[0074] CH2=C(R 1 )COOR 2 (1)
[0075] Here, R in the above formula (1) 1 is a hydrogen atom or a methyl group, R 2 is a chain alkyl group having 1 to 20 carbon atoms (hereinafter, this range of carbon atoms may be referred to as "C1-20"). 2 It is preferably a C1-14 chain alkyl group, more preferably a C2-10 chain alkyl group, and still more preferably a C4-8 chain alkyl group. Here, the chain includes both straight chain and branched chain.
[0076] As R 2The (meth)acrylic acid alkyl esters having a linear alkyl group of C1-20 include, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, and (meth)acrylate. The alkyl (meth)acrylates may be nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, etc. These alkyl (meth)acrylates may be either one or two or more.
[0077] As the alkyl (meth)acrylate, preferably, n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) are mentioned because the effects of the present invention can be more effectively exhibited.
[0078] From the viewpoint of further demonstrating the effect of the present invention, the content ratio of the alkyl (meth)acrylate in all monomer components used for the synthesis of the acrylic polymer is preferably 55% by weight or more, more preferably 60% by weight or more, further preferably 65% by weight or more, further preferably 70% by weight or more, particularly preferably 85% by weight or more, and most preferably 90% by weight or more. The upper limit of the content ratio of the alkyl (meth)acrylate is preferably 99.5% by weight or less, more preferably 99% by weight or less. However, the acrylic polymer can also be obtained by substantially polymerizing only the alkyl (meth)acrylate.
[0079] Using R 2 In the case of a (meth)acrylic acid alkyl ester having a C4-8 chain alkyl group, from the viewpoint of further exhibiting the effect of the present invention, among the (meth)acrylic acid alkyl esters contained in the monomer component, R 2 The ratio of the (meth)acrylic acid alkyl ester having a C4-8 chain alkyl group is preferably 50% by weight or more, more preferably 70% by weight or more, further preferably 90% by weight or more, particularly preferably 95% by weight or more, and most preferably 99% to 100% by weight.
[0080] As one embodiment (I) of the acrylic polymer, an acrylic polymer in which 80% by weight or more of all monomer components is n-butyl acrylate (BA) can be cited. In this case, from the perspective of further demonstrating the effects of the present invention, the content ratio of n-butyl acrylate (BA) in all monomer components is preferably 82% by weight to 99% by weight, preferably 85% by weight to 98% by weight, more preferably 87% by weight to 97% by weight, particularly preferably 89% by weight to 96% by weight, and most preferably 91% by weight to 95% by weight.
[0081] As another embodiment (II) of the acrylic polymer, an acrylic polymer in which 50% by weight or more and less than 80% by weight of the total monomer components is n-butyl acrylate (BA) can be cited. In this case, from the perspective of being able to further demonstrate the effect of the present invention, the content ratio of n-butyl acrylate (BA) in the total monomer components is preferably 52% by weight to 80% by weight, more preferably 55% by weight to 80% by weight, further preferably 60% by weight to 80% by weight, particularly preferably 63% by weight to 80% by weight, and most preferably 65% by weight to 80% by weight. In this embodiment, the total monomer components may further contain 2-ethylhexyl acrylate (2EHA) at a ratio less than n-butyl acrylate (BA).
[0082] As another embodiment (III) of the acrylic polymer, an acrylic polymer in which less than 50% by weight of the total monomer components is 2-ethylhexyl acrylate (2EHA) can be cited. In this case, from the perspective of being able to further demonstrate the effects of the present invention, the content ratio of 2-ethylhexyl acrylate (2EHA) in the total monomer components is preferably higher than 0% by weight and less than 48% by weight, more preferably 5% to 45% by weight, further preferably 10% to 43% by weight, particularly preferably 15% to 40% by weight, and most preferably 20% to 35% by weight. The total monomer components may further contain n-butyl acrylate (BA) at a ratio greater than 2-ethylhexyl acrylate (2EHA).
[0083] As another embodiment (IV) of the acrylic polymer, an acrylic polymer in which 50% by weight or more of the total monomer components are n-butyl acrylate (BA), and less than 50% by weight of the total monomer components are 2-ethylhexyl acrylate (2EHA) can be cited. In this case, from the perspective of being able to further demonstrate the effects of the present invention, the content ratio of n-butyl acrylate (BA) in the total monomer components is preferably 52% by weight to 80% by weight, more preferably 55% by weight to 80% by weight, further preferably 60% by weight to 80% by weight, particularly preferably 63% by weight to 80% by weight, and most preferably 65% by weight to 80% by weight. In addition, in this case, from the perspective of being able to further demonstrate the effects of the present invention, the content ratio of 2-ethylhexyl acrylate (2EHA) in the total monomer components is preferably higher than 0% by weight and less than 48% by weight, more preferably 5% by weight to 45% by weight, further preferably 10% by weight to 43% by weight, particularly preferably 15% by weight to 40% by weight, and most preferably 20% by weight to 35% by weight.
[0084] In the acrylic polymer, other monomers (A) may be copolymerized within the scope of not impairing the effect of the present invention. Other monomers (A) may be only one kind or more than two kinds. Other monomers (A) may be used, for example, for the purpose of adjusting the glass transition temperature (Tg) of the acrylic polymer, adjusting the adhesive properties, etc. As other monomers (A) that can improve the cohesive force and heat resistance of the adhesive, for example, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, cyanide group-containing monomers, vinyl esters, aromatic vinyl compounds, etc., are listed, preferably vinyl esters. As specific examples of vinyl esters, for example, vinyl acetate (VAc), vinyl propionate, vinyl laurate, etc. are listed, preferably vinyl acetate (VAc).
[0085] The content of other monomers (A) in all monomer components is preferably 0.001 to 40% by weight, more preferably 0.01 to 40% by weight, further preferably 0.1 to 20% by weight, particularly preferably 0.5 to 10% by weight, and most preferably 1 to 5% by weight.
[0086] In the acrylic polymer, other monomers (B) may be copolymerized within the range that does not impair the effect of the present invention. The other monomers (B) may be only one kind or two or more kinds. The other monomers (B) are other monomers that help introduce functional groups that can become crosslinking bases into the acrylic polymer or improve the adhesive force, and examples thereof include hydroxyl (OH) group-containing monomers, carboxyl group-containing monomers, acid anhydride group-containing monomers, amide group-containing monomers, amino group-containing monomers, imide group-containing monomers, epoxy group-containing monomers, (meth)acryloyl morpholine, vinyl ethers, etc.
[0087] As one embodiment of the acrylic polymer, an acrylic polymer copolymerized with a carboxyl group-containing monomer as other monomer (B) can be cited. As the carboxyl group-containing monomer, for example, acrylic acid (AA), methacrylic acid (MAA), carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc. can be cited. Among these, from the aspect of being able to further demonstrate the effect of the present invention, as the carboxyl group-containing monomer, acrylic acid (AA) and methacrylic acid (MAA) can be preferably cited, and acrylic acid (AA) is more preferred.
[0088] When a carboxyl group-containing monomer is used as the other monomer (B), from the perspective of being able to further demonstrate the effect of the present invention, the content ratio of the other monomer (B) in the total monomer components is preferably 0.1% by weight to 10% by weight, more preferably 0.2% by weight to 8% by weight, further preferably 0.5% by weight to 5% by weight, particularly preferably 0.7% by weight to 4% by weight, and most preferably 1% by weight to 3% by weight.
[0089] In the acrylic polymer, other monomers (C) may be copolymerized within the range that does not impair the effect of the present invention. The other monomers (C) may be only one kind or may be two or more kinds. Examples of other monomers (C) include hydroxyl-containing monomers. Examples of hydroxyl-containing monomers include: hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate; N-hydroxyethyl (meth)acrylamide; and the like. Among these, as hydroxyl-containing monomers, from the perspective of being able to further demonstrate the effect of the present invention, preferably, hydroxyalkyl (meth)acrylates having a linear alkyl group with 2 to 4 carbon atoms are included, and specifically, for example, 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA) are included.
[0090] When a hydroxyl-containing monomer is used as the other monomer (C), from the perspective of being able to further demonstrate the effect of the present invention, the content ratio of the other monomer (C) in the total monomer components is preferably 0.001% by weight to 10% by weight, more preferably 0.01% by weight to 5% by weight, further preferably 0.02% by weight to 2% by weight, particularly preferably 0.03% by weight to 1% by weight, and most preferably 0.04% by weight to 0.5% by weight.
[0091] From the perspective of being able to further demonstrate the effects of the present invention, the Tg of the base polymer may be, for example, above -80°C. From the perspective of improving the deformability of the adhesive layer in the shear direction, the base polymer (suitably an acrylic polymer) may be designed in such a way that the Tg is preferably below -15°C. In some embodiments, the Tg of the base polymer is, for example, preferably below -25°C, more preferably below -40°C, and further preferably below -50°C. From the perspective of improving cohesion and shape recovery, the Tg of the base polymer may be designed in such a way that the Tg is preferably above -70°C (more preferably above -65°C, and further preferably above -60°C).
[0092] The Tg of the base polymer refers to the value obtained by the Fox formula based on the Tg of the individual polymers (homopolymers) of the monomers constituting the base polymer and the weight fraction (copolymerization ratio based on weight) of the monomers. The Fox formula is shown below and is a relationship between the Tg of the copolymer and the glass transition temperature Tgi of the homopolymer formed by homopolymerizing the monomers constituting the copolymer.
[0093] 1 / Tg=Σ(Wi / Tgi)
[0094] In the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K). As Tg of the homopolymer, the value described in the known literature is adopted.
[0095] Specifically, for example, the following values can be adopted as Tg of the homopolymer.
[0096]
[0097] For the Tg of homopolymers other than those exemplified above, the values described in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. When multiple values are described in the above "Polymer Handbook", the conventional value is used. For monomers not described in the above "Polymer Handbook", the catalog values of the monomer manufacturing company are used. For the Tg of homopolymers of monomers that are not described in the above "Polymer Handbook" and the catalog values of the monomer manufacturing company are not provided, the values obtained by the measurement method described in Japanese Patent Gazette No. 2007-51271 are used.
[0098] As a method for obtaining an acrylic polymer, for example, various polymerization methods known as synthetic methods for acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization, can be appropriately adopted. Among these polymerization methods, solution polymerization can be preferably used. As a monomer supply method when performing solution polymerization, a one-time input method, a continuous supply (drip) method, a batch supply (drip) method, etc., can be appropriately adopted. The polymerization temperature can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., preferably above 20°C, more preferably above 30°C, further preferably above 40°C, preferably below 170°C, more preferably below 160°C, and further preferably below 140°C. As a method for obtaining an acrylic polymer, active energy ray irradiation polymerization such as photopolymerization by irradiation with UV light (typically carried out in the presence of a photopolymerization initiator), and radiation polymerization by irradiation with radiation such as β rays and γ rays can be adopted.
[0099] The solvent (polymerization solvent) used in solution polymerization can be appropriately selected from any appropriate organic solvent, for example, aromatic compounds such as toluene (typically aromatic hydrocarbons), acetates such as ethyl acetate, aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane, etc.
[0100] The initiator (polymerization initiator) used in the polymerization can be appropriately selected from any appropriate polymerization initiator according to the type of polymerization method. The polymerization initiator can be only one or more than two. As such a polymerization initiator, for example, there can be listed: azo polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN); persulfates such as potassium persulfate; peroxide initiators such as benzoyl peroxide and hydrogen peroxide; substituted ethane initiators such as phenyl substituted ethane; aromatic carbonyl compounds; etc. As other examples of polymerization initiators, redox initiators based on a combination of peroxides and reducing agents can be listed.
[0101] The amount of the polymerization initiator used is preferably 0.005 to 1 part by weight, more preferably 0.01 to 1 part by weight, based on 100 parts by weight of all monomer components.
[0102] The Mw of the acrylic polymer is preferably 10×10 4 ~500×10 4 , more preferably 10×10 4 ~150×10 4 , more preferably 20×10 4 ~75×10 4 , particularly preferably 35×10 4 ~65×10 4Here, Mw refers to a value obtained by GPC (gel permeation chromatography) in terms of standard polystyrene. As a GPC apparatus, for example, a model "HLC-8320GPC" (column: TSKgel GMH-H(S), manufactured by Tosoh Corporation) can be used.
[0103] (Tackifying resin)
[0104] From the perspective of being able to further demonstrate the effects of the present invention, the acrylic adhesive may include a tackifying resin. As the tackifying resin, for example, rosin-based tackifying resins, terpene-based tackifying resins, hydrocarbon-based tackifying resins, epoxy-based tackifying resins, polyamide-based tackifying resins, elastic-based tackifying resins, phenol-based tackifying resins, ketone-based tackifying resins, etc. can be listed. The tackifying resin can be only one kind or two or more kinds.
[0105] From the perspective of further demonstrating the effects of the present invention, the amount of the tackifier resin used is preferably 5 to 70 parts by weight, more preferably 10 to 60 parts by weight, further preferably 15 to 50 parts by weight, further preferably 20 to 45 parts by weight, and particularly preferably 25 to 40 parts by weight, relative to 100 parts by weight of the base polymer.
[0106] From the perspective of being able to further demonstrate the effects of the present invention, the tackifier resin preferably includes a tackifier resin TL having a softening point lower than 105°C. The tackifier resin TL can effectively contribute to improving the deformability of the adhesive layer in the surface direction (shear direction). From the perspective of obtaining a higher deformability improvement effect, the softening point of the tackifier resin used as the tackifier resin TL is preferably 50°C to 103°C, more preferably 60°C to 100°C, further preferably 65°C to 95°C, particularly preferably 70°C to 90°C, and most preferably 75°C to 85°C.
[0107] The softening point of the tackifying resin is defined as the value measured based on the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is quickly melted at the lowest possible temperature, and it is filled into a ring placed on a flat metal plate without bubbles. After cooling, the portion that is raised from the plane including the upper end of the ring is cut off with a slightly heated knife. Next, a support (ring stand) is placed in a glass container (heating bath) with a diameter of more than 85 mm and a height of more than 127 mm, and glycerin is injected until the depth becomes more than 90 mm. Next, a steel ball (diameter 9.5 mm, weight 3.5 g) and the ring filled with the sample are immersed in glycerin in a non-contact manner, and the temperature of the glycerin is maintained at 20°C ± 5°C for 15 minutes. Next, a steel ball is placed in the center of the surface of the sample in the ring and placed in a fixed position on the support. Next, keep the distance from the upper end of the ring to the glycerin surface at 50 mm, place a thermometer so that the center of the mercury ball of the thermometer is at the same height as the center of the ring, and heat the container. Make the flame of the Bunsen burner used in heating contact the center of the bottom of the container and the midpoint of the edge to make the heating uniform. It should be noted that the rate of increase in the bath temperature after reaching 40°C from the start of heating must be 5.0±0.5°C per minute. Read the temperature when the sample gradually softens and falls from the circulation and finally contacts the bottom plate, and use it as the softening point. The softening point is measured at more than 2 times at the same time, and the average value is adopted.
[0108] The amount of the tackifier resin TL used is preferably 5 to 50 parts by weight, more preferably 10 to 45 parts by weight, further preferably 15 to 40 parts by weight, particularly preferably 20 to 35 parts by weight, and most preferably 25 to 32 parts by weight, relative to 100 parts by weight of the base polymer, in order to further demonstrate the effects of the present invention.
[0109] As the tackifier resin TL, one or more types appropriately selected from the tackifier resins exemplified above having a softening point lower than 105° C. can be used. The tackifier resin TL preferably contains a rosin-based resin.
[0110] Examples of rosin-based resins that can be preferably used as the tackifier resin TL include rosin esters such as unmodified rosin esters and modified rosin esters. Examples of modified rosin esters include hydrogenated rosin esters.
[0111] From the viewpoint of further demonstrating the effects of the present invention, the tackifier resin TL preferably contains hydrogenated rosin ester. From the viewpoint of further demonstrating the effects of the present invention, the hydrogenated rosin ester preferably has a softening point of less than 105°C, more preferably 50°C to 100°C, further preferably 60°C to 90°C, particularly preferably 70°C to 85°C, and most preferably 75°C to 85°C.
[0112] The tackifier resin TL may also contain non-hydrogenated rosin esters. Here, non-hydrogenated rosin esters are a concept that collectively refers to rosin esters other than hydrogenated rosin esters among the above-mentioned rosin esters. Examples of non-hydrogenated rosin esters include unmodified rosin esters, disproportionated rosin esters, and polymerized rosin esters.
[0113] The non-hydrogenated rosin ester preferably has a softening point of less than 105°C, more preferably 50°C to 100°C, further preferably 60°C to 90°C, particularly preferably 70°C to 85°C, and most preferably 75°C to 85°C, from the viewpoint of further exhibiting the effects of the present invention.
[0114] The tackifier resin TL may contain other tackifier resins in addition to the rosin resin. As other tackifier resins, one or more tackifier resins appropriately selected from the tackifier resins exemplified above having a softening point lower than 105° C. may be used. The tackifier resin TL may contain, for example, a rosin resin and a terpene resin.
[0115] From the viewpoint of further exhibiting the effects of the present invention, the content of the rosin-based resin in the entire tackifier resin TL is preferably higher than 50 wt %, more preferably 55 to 100 wt %, further preferably 60 to 99 wt %, particularly preferably 65 to 97 wt %, and most preferably 75 to 97 wt %.
[0116] From the viewpoint of further exhibiting the effects of the present invention, the tackifier resin may include a tackifier resin TL in combination with a tackifier resin TH having a softening point of 105° C. or higher (preferably 105° C. to 170° C.).
[0117] As the tackifier resin TH, one or more appropriately selected from the tackifier resins having a softening point of 105° C. or higher can be used among the tackifier resins exemplified above. The tackifier resin TH may include at least one selected from rosin-based tackifier resins (e.g., rosin esters) and terpene-based tackifier resins (e.g., terpene phenol resins).
[0118] (Crosslinking agent)
[0119] The acrylic adhesive may contain a crosslinking agent. The crosslinking agent may be only one or more than two. By using the crosslinking agent, the acrylic adhesive can be given a moderate cohesive force. The crosslinking agent can also contribute to the adjustment of the offset distance and the return distance in the holding force test. The acrylic adhesive containing a crosslinking agent can be obtained, for example, by forming an adhesive layer using an adhesive composition containing the crosslinking agent. The crosslinking agent can be contained in the acrylic adhesive in a form after the crosslinking reaction, a form before the crosslinking reaction, a form partially subjected to the crosslinking reaction, an intermediate or composite form thereof, etc. The crosslinking agent is typically contained in the acrylic adhesive in a form mainly after the crosslinking reaction.
[0120] From the perspective of further exhibiting the effects of the present invention, the amount of the cross-linking agent used is preferably 0.005 to 10 parts by weight, more preferably 0.01 to 7 parts by weight, further preferably 0.05 to 5 parts by weight, particularly preferably 0.1 to 4 parts by weight, and most preferably 1 to 3 parts by weight, relative to 100 parts by weight of the base polymer.
[0121] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, silicone crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, alkyl etherified melamine crosslinking agents, metal chelate crosslinking agents, peroxide crosslinking agents, and the like. From the perspective of further demonstrating the effects of the present invention, isocyanate crosslinking agents and epoxy crosslinking agents are preferred, and isocyanate crosslinking agents are more preferred.
[0122] The isocyanate crosslinking agent may be a compound having two or more isocyanate groups (including isocyanate regeneration type functional groups in which the isocyanate groups are temporarily protected by a blocking agent or polymerization) in one molecule. Examples of the isocyanate crosslinking agent include aromatic isocyanates such as toluene diisocyanate and xylylene diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; aliphatic isocyanates such as hexamethylene diisocyanate; and the like.
[0123] More specifically, examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic diisocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, and polymethylene polyphenyl isocyanate; trimethylolpropane / toluene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: CORONATE L), trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., manufactured by Tosoh Corporation, trade name: CORONATE HL), isocyanurate of hexamethylene diisocyanate (e.g., manufactured by Tosoh Corporation, trade name: CORONATE 3), and isocyanurate of hexamethylene diisocyanate (e.g., manufactured by Tosoh Corporation, trade name: CORONATE 4). isocyanate adducts such as trimethylolpropane adducts of xylylene diisocyanate (e.g., manufactured by Mitsui Chemicals, Inc., trade name: TAKENATE D110N), trimethylolpropane adducts of xylylene diisocyanate (e.g., manufactured by Mitsui Chemicals, Inc., trade name: TAKENATE D120N), trimethylolpropane adducts of isophorone diisocyanate (e.g., manufactured by Mitsui Chemicals, Inc., trade name: TAKENATE D140N), trimethylolpropane adducts of hexamethylene diisocyanate (e.g., manufactured by Mitsui Chemicals, Inc., trade name: TAKENATE D160N); polyether polyisocyanates, polyester polyisocyanates, and adducts thereof with various polyols; polyisocyanates multifunctionalized by isocyanurate bonds, biuret bonds, allophanate bonds, etc.; etc. Among these, aromatic isocyanate and alicyclic isocyanate are preferred because they can achieve both deformability and cohesive force in a good balance.
[0124] From the viewpoint of further exhibiting the effects of the present invention, the amount of the isocyanate crosslinking agent used is preferably 0.005 to 10 parts by weight, more preferably 0.01 to 7 parts by weight, further preferably 0.05 to 5 parts by weight, particularly preferably 0.1 to 4 parts by weight, and most preferably 1 to 3 parts by weight, relative to 100 parts by weight of the base polymer.
[0125] When the monomer components constituting the acrylic polymer include a hydroxyl-containing monomer, the weight ratio of the isocyanate crosslinking agent / hydroxyl-containing monomer is preferably higher than 20 and lower than 50, more preferably 22 to 45, further preferably 25 to 40, particularly preferably 27 to 40, and most preferably 30 to 35, from the viewpoint of being able to further express the effects of the present invention.
[0126] When the acrylic adhesive contains a tackifier resin TL having a softening point of 105° C. or less, the weight ratio of the tackifier resin TL / isocyanate crosslinking agent is preferably higher than 2 and lower than 15, more preferably 5 to 13, further preferably 7 to 12, and particularly preferably 7 to 11, from the perspective of further exhibiting the effects of the present invention.
[0127] As the epoxy crosslinking agent, a polyfunctional epoxy compound having two or more epoxy groups in one molecule can be used. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl meta-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and sorbitol polyglycidyl ether. Glycerol ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, epoxy resin having two or more epoxy groups in the molecule, etc. Commercially available products of epoxy crosslinking agents include, for example, trade names "TETRAD C" and "TETRAD X" manufactured by Mitsubishi Gas Chemical Co., Ltd.
[0128] From the viewpoint of further exhibiting the effects of the present invention, the amount of the epoxy crosslinking agent used is preferably 0.005 to 10 parts by weight, more preferably 0.01 to 5 parts by weight, further preferably 0.015 to 1 part by weight, further preferably 0.015 to 0.5 parts by weight, particularly preferably 0.015 to 0.3 parts by weight, and most preferably 0.15 to 0.3 parts by weight, relative to 100 parts by weight of the base polymer.
[0129] (Other ingredients)
[0130] The acrylic adhesive may contain various additives commonly used in the field of adhesives, such as colorants (pigments, dyes, etc.), leveling agents, crosslinking aids, plasticizers, softeners, fillers, antistatic agents, anti-aging agents, ultraviolet absorbers, antioxidants, and light stabilizers, as needed. For such various additives, conventionally known additives can be used by conventional methods.
[0131] When a colorant (pigment, dye, etc.) is used as another component, its usage amount is preferably 0.001 to 10 parts by weight, more preferably 0.01 to 5 parts by weight, further preferably 0.05 to 1 part by weight, and particularly preferably 0.1 to 1 part by weight, relative to 100 parts by weight of the base polymer.
[0132] ""use""
[0133] The double-sided adhesive tape according to the embodiment of the present invention has excellent impact absorption over a wide temperature range, particularly in a low temperature region. Utilizing this feature, the double-sided adhesive tape according to the embodiment of the present invention can be used as an impact absorption tape for a display, for example.
[0134] Example
[0135] The present invention is described in more detail below with reference to the following examples and comparative examples. However, the present invention is not limited thereto. It should be noted that, in the following description, "parts" and "%" refer to weight basis unless otherwise specified.
[0136] <Measurement of Storage Modulus E' of Double-Sided Adhesive Tape as a Whole>
[0137] As a dynamic viscoelasticity measuring device, RSA-G2 (TA Instruments Japan Inc.) was used, and a sample with a sheet width of 10 mm was set in the tensile fixture of the measuring device at a measuring interval of 20 mm, and the measuring environment oven was changed to the measuring start temperature. After confirming that the temperature of the measuring environment has stabilized, the temperature was raised at a temperature rise rate of 5°C / min from the lower limit temperature of the temperature in the specified temperature range of the measurement. The frequency during the measurement was 1 Hz, and tensile deformation was applied. While controlling the deformation strain in the area where the sheet would not undergo permanent deformation, the generated stress was calculated as the storage modulus E'.
[0138] <Measurement of Storage Modulus E' of Substrate Layer>
[0139] As a dynamic viscoelasticity measuring device, RSA-G2 (TA Instruments Japan Inc.) was used, and a sample with a sheet width of 10 mm was set in the tensile fixture of the measuring device at a measuring interval of 20 mm, and the measuring environment oven was changed to the measuring start temperature. After confirming that the temperature of the measuring environment has stabilized, the temperature was raised at a temperature rise rate of 5°C / min from the lower limit temperature of the temperature in the specified temperature range of the measurement. The frequency during the measurement was 1 Hz, and tensile deformation was applied. While controlling the deformation strain in the area where the sheet would not undergo permanent deformation, the generated stress was calculated as the storage modulus E'.
[0140] <Measurement of Storage Modulus G' of Adhesive Layer>
[0141] As a dynamic viscoelasticity measuring device, ARES-G2 (TA Instruments Japan Inc.) was used, and a sample with a sheet thickness of 1 mm to 2 mm was set in the specified measuring device fixture, and the measuring environment oven was changed to the measuring start temperature. After confirming that the temperature of the measuring environment has stabilized, the temperature was raised at a temperature rise rate of 5°C / min from the lower limit temperature of the temperature in the specified temperature range of the measurement. The frequency during the measurement was 1 Hz, and shear deformation was applied. While controlling the deformation strain in the area where the sheet would not undergo permanent deformation, the generated stress was calculated as the storage modulus G'.
[0142] <Adhesion>
[0143] Adhesion refers to the 180-degree peel strength (180-degree peel adhesion) to a stainless steel plate. Regarding the 180-degree peel strength, a single-sided adhesive tape (trade name "No.31B", manufactured by Nitto Denko Corporation, total thickness 50 μm) was pasted on the surface of any of the two adhesive layers of the adhesive sheet, and the adhesive sheet was cut into a measurement sample with a size of 20 mm wide and 100 mm long. Under an environment of 23°C and 50% RH, a 2 kg roller was moved back and forth once to press the adhesive surface of the above measurement sample against the surface of a stainless steel plate (SUS304BA plate). After leaving it in this environment for 30 minutes, the peel strength (N / 20mm) was measured using a universal tensile compression tester in accordance with JIS Z 0237:2000 at a tensile speed of 300 mm / min and a peeling angle of 180 degrees. As a universal tensile compression tester, the product name "Autograph AG-10G tensile tester" manufactured by Shimadzu Corporation was used.
[0144] <Shock Absorption>
[0145] The impact absorption is expressed by the pressure when an iron ball is dropped. A double-sided adhesive tape cut into 70 mm × 70 mm is placed on a stainless steel plate (SUS plate: 10 mm × 150 mm × 150 mm) with the center overlapped, a 70 mm × 70 mm pressure measuring film (manufactured by Fuji Film Co., Ltd., Prescale (MS type)) is placed on it with the center overlapped, and a stainless steel plate (SUS plate: 5 mm × 70 mm × 70 mm) is placed on it with the center overlapped, and an iron ball (96 g) is dropped from a height of 40 cm toward the center. Then, the pressure measuring film is taken out, and the image is read using a pressure image analysis device scanner GT-F740 (manufactured by Fuji Film Co., Ltd.), and the pressure is analyzed using a Prescale pressure image analysis system FPD-8010J (manufactured by Fuji Film Co., Ltd.).
[0146] [Example 1]
[0147] Into a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet pipe and a condenser, 68 parts of n-butyl acrylate (BA), 29 parts of 2-ethylhexyl acrylate (2EHA), 3 parts of acrylic acid (AA) and 0.04 parts of 4-hydroxybutyl acrylate (4HBA) as monomer components, 0.07 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and 151 parts of toluene as a polymerization solvent were added, and solution polymerization was carried out at 65° C. for 5 hours and further at 80° C. for 2 hours to obtain a toluene solution of an acrylic polymer (A). The weight average molecular weight of the acrylic polymer (A) was 440,000.
[0148] To 100 parts of the acrylic polymer (A) contained in the toluene solution, 30 parts of a tackifier resin (manufactured by Harima Chemicals, Inc., hydrogenated rosin glycerol ester, trade name "HARITACK SE10") and 3 parts of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added to prepare an adhesive composition (A).
[0149] Two commercially available release liners (manufactured by Mitsubishi Chemical, trade name "Diafoil MRF#50" (a biaxially oriented polyester film release liner with a release treatment layer on one side, thickness 50 μm)) were prepared. The above-mentioned adhesive composition (A) was applied to one side (release side) of each release liner so that the thickness after drying was 50 μm, and dried at 120° C. for 5 minutes. In this way, an adhesive layer (first adhesive layer and second adhesive layer) with a thickness of 50 μm composed of an acrylic adhesive (A) corresponding to the adhesive composition (A) was formed on the release sides of the above two release liners, respectively.
[0150] As a substrate layer, a thermosetting polyurethane resin film with a thickness of 100 μm is prepared (a polycaprolactone (ester) polyurethane resin film with a thickness of 100 μm (100% modulus = 1.8 MPa) manufactured by Toray Industries, Ltd.). The first adhesive layer and the second adhesive layer formed on the above-mentioned two release liners are bonded to the first and second surfaces of the substrate layer. The above-mentioned release liner remains directly on the adhesive layer and is used to protect the surface (adhesive surface) of the adhesive layer. The obtained structure is passed through a laminator at 80°C (0.3 MPa, speed 0.5 m / min) once, and then aged in an oven at 50°C for 3 days. In this way, an adhesive tape (1) is obtained.
[0151] The results are shown in Table 1.
[0152] [Example 2]
[0153] Into a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet pipe and a condenser, 100 parts of n-butyl acrylate (BA), 5 parts of vinyl acetate (VAc), 3 parts of acrylic acid (AA) and 0.1 parts of 2-hydroxyethyl acrylate (HEA) as monomer components, 0.25 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and 200 parts of toluene as a polymerization solvent were added, and solution polymerization was carried out at 60° C. for 6 hours and further at 75° C. for 3 hours to obtain a toluene solution of an acrylic polymer (B). The weight average molecular weight of the acrylic polymer (B) was 550,000.
[0154] To 100 parts of the acrylic polymer (B) contained in the toluene solution, 10 parts of a tackifier resin (polymerized rosin ester manufactured by Harima Chemicals, Inc., trade name "HARITACK PCJ"), 10 parts of a tackifier resin (hydrogenated rosin glycerol ester manufactured by Harima Chemicals, Inc., trade name "HARITACK SE10"), 5 parts of a tackifier resin (Rika Hercules Inc., trade name "HERCOLYN D"), 15 parts of a phenol-modified rosin (Sumitomo Bakelite Co., Ltd., trade name "SUMILITE PR12603N"), and 2 parts of an isocyanate crosslinking agent (Tosoh Corporation, trade name "CORONATE L") were added to prepare an adhesive composition (B).
[0155] Two commercially available release liners (manufactured by Mitsubishi Chemical, trade name "Diafoil MRF#50" (a biaxially oriented polyester film release liner with a release treatment layer on one side, thickness 50 μm)) were prepared. The above-mentioned adhesive composition (B) was applied to one side (release side) of each release liner so that the thickness after drying was 50 μm, and dried at 120°C for 5 minutes. In this way, an adhesive layer (first adhesive layer and second adhesive layer) with a thickness of 50 μm consisting of an acrylic adhesive (B) corresponding to the adhesive composition (B) was formed on the release sides of the above two release liners, respectively.
[0156] As a substrate layer, a thermosetting polyurethane resin film (a polycaprolactone (ester) polyurethane resin film (100% modulus = 1.8 MPa) with a thickness of 100 μm, manufactured by Toray Industries, Inc.) is prepared. The first adhesive layer and the second adhesive layer formed on the above-mentioned two release liners are bonded to the first and second surfaces of the substrate layer. The above-mentioned release liner remains directly on the adhesive layer and is used to protect the surface (adhesive surface) of the adhesive layer. The obtained structure is passed through a laminator at 80°C (0.3 MPa, speed 0.5 m / min) once, and then aged in an oven at 50°C for 3 days. In this way, an adhesive tape (2) is obtained.
[0157] The results are shown in Table 1.
[0158] [Example 3]
[0159] Into a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet pipe and a condenser, 100 parts of n-butyl acrylate (BA), 3 parts of vinyl acetate (VAc), 2 parts of acrylic acid (AA) and 0.2 parts of 2-hydroxyethyl acrylate (HEA) as monomer components, 0.25 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and 200 parts of toluene as a polymerization solvent were added, and solution polymerization was carried out at 60° C. for 6 hours and further at 75° C. for 3 hours to obtain a toluene solution of an acrylic polymer (C). The weight average molecular weight of the acrylic polymer (C) was 600,000.
[0160] To 100 parts of the acrylic polymer (C) contained in the toluene solution, 10 parts of a tackifier resin (Harima Chemicals, Inc., polymerized rosin ester, trade name "HARITACK PCJ"), 10 parts of a tackifier resin (Harima Chemicals, Inc., hydrogenated rosin glycerol ester, trade name "HARITACK SE10"), 5 parts of a tackifier resin (Rika Hercules Inc., trade name "HERCOLYN D"), 15 parts of a phenol-modified rosin (Sumitomo Bakelite Co., Ltd., trade name "SUMILITE PR12603N"), 2 parts of an isocyanate crosslinking agent (Tosoh Corporation, trade name "CORONATE L"), and 0.2 parts of a black pigment (Dainichi Seika Industries, "NAF-5091Black") were added to prepare an adhesive composition (C).
[0161] Two commercially available release liners (manufactured by Mitsubishi Chemical, trade name "Diafoil MRF#50" (a biaxially oriented polyester film release liner with a release treatment layer on one side, thickness 50 μm)) were prepared. The above-mentioned adhesive composition (C) was applied to one side (release side) of each release liner in such a manner that the thickness after drying was 50 μm, and dried at 120° C. for 5 minutes. In this way, an adhesive layer (first adhesive layer and second adhesive layer) with a thickness of 50 μm composed of an acrylic adhesive (C) corresponding to the adhesive composition (C) was formed on the release sides of the above two release liners, respectively.
[0162] 50 parts of toluene, 330 parts of polytetramethylene glycol (PTMG2000 manufactured by Mitsubishi Chemical Corporation), 50 parts of hexamethylene diisocyanate, 2 parts of hexamethylene diisocyanate isocyanurate-modified (TAKENATE (registered trademark) D-170N manufactured by Mitsui Chemicals, Inc.), 0.02 parts of dibutyltin dilaurate, 0.02 parts of hydroquinone monomethyl ether, and 11 parts of 2-hydroxyethyl acrylate were mixed, maintained at 70° C. for 5 hours, and then diluted with toluene to obtain a toluene solution of oligomer A having a solid content concentration of 60% by weight. 100 parts of a toluene solution of the obtained oligomer (P) having a solid content concentration of 60% by weight, 5 parts of a hindered phenol-based antioxidant (IRGANOX 1010, manufactured by BASF Japan Co., Ltd.), and 1.5 parts of a photopolymerization initiator (IRGACURE 184, manufactured by BASF Japan Co., Ltd.) were mixed, and diluted with methyl ethyl ketone to obtain a coating composition (Q) for forming a resin thin film having a solid content concentration of 40% by weight.
[0163] As a supporting substrate, a polyester film with a thickness of 50 μm and a release layer (manufactured by Toray Industries, Ltd., trade name "LUMIRROR (registered trademark) R75X") was used. A continuous coating device based on a slit coater was used to adjust the discharge flow rate, and the coating composition (Q) for forming a resin film was applied to the release layer of the supporting substrate in such a manner that the thickness of the cured resin film was 100 μm, and the film was dried and cured. The resin film was peeled off from the supporting substrate to obtain a thermosetting urethane acrylate resin film (R) with a thickness of 100 μm (100% modulus = 2.0 MPa). It should be noted that the drying temperature was set to 80°C, and the curing conditions of ultraviolet rays (UV rays) were set to an irradiation output of 400 mW / cm 2 , cumulative light intensity 1200mJ / cm 2 .
[0164] The obtained thermosetting urethane acrylate resin film (R) is used as a substrate layer, and the first adhesive layer and the second adhesive layer formed on the above two release liners are bonded to the first and second surfaces of the substrate layer. The above release liners remain directly on the adhesive layer and are used to protect the surface (adhesive surface) of the adhesive layer. The obtained structure is passed through a laminator at 80°C (0.3MPa, speed 0.5m / min) once, and then aged in an oven at 50°C for 3 days. In this way, an adhesive tape (3) is obtained.
[0165] The results are shown in Table 1.
[0166] [Example 4]
[0167] A pressure-sensitive adhesive tape (4) was obtained in the same manner as in Example 3 except that the amount of the black pigment ("NAF-5091Black" manufactured by Dainichi Seika Industries) was changed to 0.6 parts.
[0168] The results are shown in Table 1.
[0169] [Example 5]
[0170] A pressure-sensitive adhesive tape (5) was obtained in the same manner as in Example 3 except that the substrate layer was changed to a thermosetting polyurethane resin film (manufactured by Toray Industries, Ltd., 100 μm thick polycaprolactone (ester) polyurethane resin film (100% modulus = 1.8 MPa).
[0171] The results are shown in Table 1.
[0172] [Example 6]
[0173] A pressure-sensitive adhesive tape (6) was obtained in the same manner as in Example 5 except that the amount of the black pigment ("NAF-5091Black" manufactured by Dainichi Seika Industries) was changed to 0.6 parts.
[0174] The results are shown in Table 1.
[0175] [Comparative Example 1]
[0176] A pressure-sensitive adhesive tape (C1) was obtained in the same manner as in Example 1 except that a 100 μm-thick thermoplastic polyurethane resin film (manufactured by Okura Industries, Ltd., urethane elastomer film, trade name “SILKLON”) was used as the substrate layer.
[0177] The results are shown in Table 1.
[0178] [Comparative Example 2]
[0179] A pressure-sensitive adhesive tape (C2) was obtained in the same manner as in Example 2 except that a 100 μm-thick thermoplastic polyurethane resin film (manufactured by Okura Industries, Ltd., urethane elastomer film, trade name “SILKLON”) was used as the substrate layer.
[0180] The results are shown in Table 1.
[0181] [Comparative Example 3]
[0182] Into a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet pipe and a condenser, 95 parts of n-butyl acrylate (BA) as monomer components, 5 parts by weight of acrylic acid (AA), 0.25 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and 234 parts of ethyl acetate as a polymerization solvent were added, and solution polymerization was carried out at 65° C. for 9 hours to obtain an ethyl acetate solution of an acrylic polymer (D). The weight average molecular weight of the acrylic polymer (D) was 600,000.
[0183] To 100 parts of the acrylic polymer (D) contained in the toluene solution, 30 parts of a tackifier resin (manufactured by Yasuhara Chemical Co., Ltd., a terpene phenol resin, trade name "YS POLYSTER S145"), 2 parts of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L"), and 0.01 parts of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C") were added to prepare an adhesive composition (D).
[0184] Two commercially available release liners (manufactured by Mitsubishi Chemical, trade name "Diafoil MRF#50" (a biaxially oriented polyester film release liner with a release treatment layer on one side, thickness 50 μm)) were prepared. The above-mentioned adhesive composition (D) was applied to one side (release side) of each release liner so that the thickness after drying was 50 μm, and dried at 120°C for 5 minutes. In this way, an adhesive layer (first adhesive layer and second adhesive layer) with a thickness of 50 μm composed of an acrylic adhesive (D) corresponding to the adhesive composition (D) was formed on the release sides of the above two release liners, respectively.
[0185] As a substrate layer, a thermosetting polyurethane resin film with a thickness of 100 μm is prepared (a polycaprolactam (ester) polyurethane resin film with a thickness of 100 μm (100% modulus = 1.8 MPa) manufactured by Toray Industries, Ltd.). The first adhesive layer and the second adhesive layer formed on the above-mentioned two release liners are bonded to the first and second surfaces of the substrate layer. The above-mentioned release liner remains directly on the adhesive layer and is used to protect the surface (adhesive surface) of the adhesive layer. The obtained structure is passed through a laminator at 80°C (0.3 MPa, speed 0.5 m / min) once, and then aged in an oven at 50°C for 3 days. In this way, an adhesive tape (C3) is obtained.
[0186] The results are shown in Table 1.
[0187] [Table 1]
[0188]
[0189] Industrial Applicability
[0190] The double-sided adhesive tape according to the embodiment of the present invention has excellent impact absorption over a wide temperature range, particularly in a low temperature region. Utilizing this feature, the double-sided adhesive tape according to the embodiment of the present invention can be used as an impact absorption tape for a display, for example.
[0191] Description of Reference Numerals
[0192] 1000 Double-sided adhesive tape
[0193] 100 Base material layer
[0194] 200a Adhesive layer
[0195] 200b Adhesive layer
Claims
1. A double-sided adhesive tape comprising an adhesive layer on both sides of a substrate layer, The storage modulus E' of the double-sided adhesive tape as a whole, measured at -25°C to 120°C and at a frequency of 1 Hz, is 5×10 5 Pa~1.0×10 8 In the range of Pa, The substrate layer comprises at least one polar functional group-containing polymer selected from condensation polymers and addition polymers, The adhesive force of the adhesive layer to a SUS plate when subjected to 180-degree peeling at a tensile speed of 300 mm / min at 23° C. and 50% RH is 5 N / 20 mm or more.
2. The double-sided adhesive tape according to claim 1, wherein The storage modulus E' of the substrate layer measured at -25°C to 120°C and at a frequency of 1 Hz is 1.0×10 5 Pa~1.0×10 8 Within the range of Pa.
3. The double-sided adhesive tape according to claim 1 or 2, wherein The maximum value of the storage modulus G' of the adhesive layer measured at -25°C to 120°C and at a frequency of 1 Hz is 1.0×10 10 Below Pa.
4. The double-sided adhesive tape according to claim 1 or 2, wherein The polar functional group-containing polymer is at least one selected from polyamide, polyurethane, and polyurea.
5. The double-sided adhesive tape according to claim 1 or 2, wherein The polar functional group-containing polymer has at least one selected from the group consisting of an ether bond and an ester bond.
6. The double-sided adhesive tape according to claim 1 or 2, wherein The adhesive layer includes at least one selected from the group consisting of acrylic adhesives, rubber adhesives, silicone adhesives, and urethane adhesives.
7. The double-sided adhesive tape according to claim 1 or 2, which is an impact-absorbing tape for displays.
Citation Information
Patent Citations
Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device
JP2007051271A
Impact absorbing material
JP2014094575A
Adhesive tape having foamed resin base material, and method for producing same
CN107109148A
Double-sided pressure-sensitive adhesive tape
JP2013249367A
Adhesive tape, method for producing the same, article and portable electronic terminal
JP2016117806A